Ethics and Politics of Translating. - Meschonnic, Henri (Benjamins translation library, 2011)
What if meaning were the last thing that mattered in language? In this essay, Henri Meschonnic explains what it means to translate the sense of language and how to do it. In a radical stand against a hermeneutical approach based on the dualistic view of the linguistic sign and against its separation into a meaningful signified and a meaningless signifier, Henri Meschonnic argues for a poetics of translating. Because texts generate meaning through their power of expression, to translate ethically involves listening to the various rhythms that characterize them: prosodic, consonantal or vocalic.